Guía metodológica de desarrollo sensomotor y perceptual de los niños y niñas de segundo año de educación básica de la escuela fiscal Luis Fernando Vivero. - Villarroel Duque, Mónica Mercedes (2015)
The sensory motor and perceptual development is essential as is basis for new learning are met. In the early life stages of growth and pre-school stage, mainly in the first and second years of basic education development should be conducted in an appropriate and consistent manner to the age of children in order that the At this level, can be performed in an appropriate and timely processes of reading, writing and calculating way. As in previous learning of literacy and mathematics stages, have not developed adequately skills senso motor and perceptual, through free and directed recreational and educational activities, children are not ready to enter these processes, being from the second year of basic education that perform the formal process of literacy. If processes are Forzan, safely difficulties will be presented, which is a real torture and torment for the children and a headache for parents and teachers. This research, part of the theoretical foundations related to sensory-perception and motor development as fundamental to prevent and avoid learning difficulties and above all with the aim of enhancing skills for new learning. From a pedagogical point of view psycho, major theories that are based on the sensory-perceptual and motor development as suggested by Piaget, Montessori and Gardner are addressed. Finally, the activities proposed in the methodological guide, are simple and may or may not be performed in sequence, using materials from the environment, every day and inexpensive for what they are possible to apply in any school, it all depends on the initiative and creativity of the teacher or educator who uses it and apply direct its work to the development of identity and culture of the people or nationality that employs.